Mining the soil myxobacteria and finding sources of anti-diabetic metabolites - Saadatpour, Fatemeh; Nikzad, Mohammad Hossain; Salimi, Fatemeh; Mohammadipanah, Fatemeh (Folia microbiologica, 2024)
Secondary metabolites produced by myxobacterial genera are often characterized as diverse molecules with unique structural properties which drove us to search for myxobacterial source of anti-diabetic drug discovery. In the present study, from 80 soil samples, out of sixty-five observed isolates, 30 and 16 were purified as Myxococcus and non-Myxococcus, respectively. Isolated strains taxonomically belonged to the genera Myxococcus, Corallococcus and Cystobacter, Archangium, Nanocystis, and Sorangium, and some could not be attributed. Secondary metabolites of selected non-Myxococcus isolates extracted by the liquid-liquid method showed that the myxobacterium UTMC 4530 demonstrated the highest inhibition on the formation of carbonyl group and fructosamine, respectively. In addition, it showed 23% and 15.8% inhibitory activity on α-glucosides and α-amylase compared to acarbose (23%, 18%), respectively. The extract of strain UTMC 4530 showed 35% induction effect on glucose adsorption while showing no radical scavenging activity and no toxic effect on HRBC lysis and HepG2 in cytotoxicity assays. The strain UTMC 4530 (ON808962), with the multiple antidiabetic activity, showed 87.3% similarity to Corallococcus llansteffanensis which indicates its affiliation to a new genus. The results of this study revealed that secondary metabolites produced by strain UTMC 4530 can be considered a promising source to find new therapeutic and pharmaceutical applications perhaps a multi-mechanism anti-diabetic compound.
Keywords: Myxococcales; Phylogeny; Anti-diabetic bioassays; půdní mikrobiologie; Myxococcus; Secondary metabolites; půda; Soil Microbiology; Cytotoxicity; Inflammation; Myxobacteria; fylogeneze; Diabetes; Soil